Digital Health Literacy and Women in India: Bridging the Chasm for a Healthier Tomorrow - Avantika Gupta; Aditi Chandrakar; Abhiruchi Galhotra (Healthline, 2025)
Digital health technologies (DHTs) can be transformative in the delivery and outcomes of healthcare, especially for women in countries like India. Despite their potential, their efficacy is undermined by existing gender-based disparities in autonomy, education, and access. This paper seeks to discuss the socio-cultural and technological factors which form barriers to women’s digital health literacy in India. Data reveals that women are disproportionately marginalized from accessing telemedicine, mHealth applications, and health information systems due to a widening gender disparity in smartphone ownership and internet usage. In India, where socio-cultural, economic, and gender-based disparities are deeply rooted, improving digital health literacy among women presents both a challenge and a crucial opportunity. Closing these gaps is critical for fostering inclusive frameworks that advance gender-sensitive, participatory healthcare systems in alignment with the Sustainable Development Goals.